Blood Pressure Levels and Maternal Outcome in Women with Preeclampsia – a Retrospective Study from a Large Tertiary Obstetric Centre - Willy, Daniela; Willy, Kevin; Köster, Helen-Ann; Braun, Janina; Möllers, Mareike; Sourouni, Marina; Klockenbusch, Walter; Schmitz, Ralf; Oelmeier, Kathrin (Geburtshilfe und Frauenheilkunde, 2022)
Introduction Patients with high blood pressure levels are at high risk for acute complications as well as serious long-term consequences. Women with preeclampsia often experience very high blood pressure levels during pregnancy and postpartum and are also known to have a higher cardiovascular risk in later life.Material and Methods In our single-centre retrospective cohort study, we analysed 158 pregnancies complicated by preeclampsia in regard to maternal outcome. We divided the patient cohort into three subgroups according to the blood pressure levels during hospital stay.Results Pre-existing arterial hypertension was significantly more common in patients with a hypertensive crisis (systolic blood pressure ≥ 180 mmHg and/or diastolic blood pressure ≥ 120 mmHg) during pregnancy than in patients with moderate or severe hypertension (p = 0.001). Women with a hypertensive crisis had an unfavourable outcome compared to women with lower blood pressure levels. These women developed a HELLP-syndrome significantly more often (p = 0.013). Moreover, most of the women with a hypertensive crisis during pregnancy were still hypertensive at hospital discharge (p = 0.004), even though they were administrated antihypertensive agents more often (p < 0.001) compared to women with lower blood pressure values.Conclusion Preeclamptic women with hypertensive crises should be identified quickly and monitored closely to avoid further complications. Standardized follow-up programs are lacking, but especially these patients seem to be at high risk for persistent hypertension and increased cardiovascular morbidity and therefore should receive specialist follow-up, including hypertensiologists, cardiologists and gynaecologists. Large prospective trials are required for a better understanding of these interrelations and to develop a specific follow-up program.
Keywords: preeclampsia; arterial hypertension; hypertensive crisis; cardiovascular risk; hypertension in pregnancy; HELLP-syndrome